Financing global development: Can foreign direct investments be increased through international investment agreements? - Axel Berger (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
The UN Conference on Financing for Development in Addis Ababa in July 2015 will pave the way for the implementation of the post-2015 development agenda. The Briefing Paper series “Financing Global Development” analyses key financial and non-financial means of implementation for the new Sustainable Development Goals (SDGs) and discusses building blocks of a new framework for development finance. Foreign direct investment (FDI) is hailed as an important source of external financing for many developing countries. Improving developing countries' access to global FDI flows is thus a central aim of the international community, as documented by the past two United Nations Conferences on Financing for Development, in Monterrey in 2002 and Doha in 2008. The need to set up a “stable and predictable investment climate” as a precondition to attract FDI was emphasised in the outcome documents of the Monterrey and Doha conferences. International investment agreements (IIAs) are mentioned as effective policy instruments to promote FDI flows. In fact, many developing countries signed IIAs to attract FDI and, in turn, promote economic development. This standard justification is increasingly being questioned by critics of IIAs. An increasing number of policy-makers, scholars and non-governmental organisations argue that IIAs, by and large, have not resulted in increased FDI flows and, worse still, they fear that IIAs excessively restrict host countries' ability to adopt public policies aimed at promoting sustainable development. Incidentally, this scepticism has also set the tone of the draft for the accord to be adopted at the Addis Ababa conference. It emphasises that FDI can have a positive impact on development, but only if foreign investors adhere to social and environmental standards, and if IIAs do not constrain domestic policy space to implement development-oriented policies. The overview of the empirical evidence on the effects of IIAs on FDI flows suggests that this scepticism is well-justified. Although various studies find a positive impact of IIAs on FDI, in light of methodological challenges to actually measure this impact and alternative evidence, these results should be interpreted with great caution. Furthermore, researchers have only recently tried to account for different treaty designs. They find that treaty content matters and not all IIAs have the same effect on FDI flows. For example, treaties with market-access provisions have a positive effect on FDI, in particular if they are included in preferential trade and investment agreements (PTIAs). The hotly debated investor-state dispute-settlement (ISDS) clauses, on the other hand, have no effect on FDI. Policy-makers in developing countries hoping to attract FDI should therefore pay closer attention to the actual design of IIAs. The empirical evidence suggests that they have some room to improve the compatibility of IIAs and national policy objectives by reformulating the standards of investment protection. In Addis Ababa, the international community should come up with proposals for how developing countries can be supported in order to reform their IIAs.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Handel und Investitionen